TAXATION OF AGRICULTURAL ACTIVITY IN POLAND: THE CURRENT STATE AND FUTURE PROSPECTS - Marian Podstawka; Łukasz Podstawka (Polityki Europejskie, Finanse i Marketing)
This study is a response to an ongoing debate on changes in the taxation of agricultural income. The current taxes applicable to farms in Poland do not concern income per se – they are property taxes which include: agricultural tax on land, forestry tax and property tax. Although these taxes do not refer to agricultural income, they are paid by it. It is important, therefore, to know how much this income is reduced by these taxes. Studies show that it is about 10%. Therefore, when a new income tax structure is introduced, its rate should not exceed 10%. The calculation of farm income in Poland will encounter many problems, such as establishing a catalogue of costs, which will include depreciation. In order to include it when calculating income, the present value of a farm’s fixed assets should first be established, which may encounter major substantive and organizational difficulties. More problems will surely follow, such as: dividing costs between household and agricultural holding, determining what a fixed asset is in the case of a farm, etc. It seems that calculating farm income is unavoidable. On the one hand, it is necessary for the potential introduction of income tax. On the other hand, having recognized the income situation of farms, one could resign from estimating losses caused by drought or other unfortunate events. Compensation could be granted due to income losses. This would be a clearer, more obvious and objective criterion. According to current practices, losses caused by unfortunate events (e.g. drought) do not always translate into losses in agricultural income, given that these losses are not always objectively estimated by the committees appointed by provincial governors. In the case of income losses, agricultural accounting data guarantee their objective appraisal. The aim of the paper is to evaluate the current situation regarding the taxation of agricultural activity and to present proposals for potential changes in the taxation of agricultural activity. Two research hypotheses were put forward: 1. the current level of taxation of income and revenue from agricultural activity with agricultural tax and property tax is symbolic, 2. in order to maintain the current tax treatment, the rate of the new tax on farm income cannot be higher than 10%. The article is based on descriptive, tabular and financial analysis methods. The sources of information were literature and FADN agricultural accounting data collected by the Institute of Agricultural and Food Economics – National Research Institute in Warsaw.